Analisis Statistical Process Control (SPC) pada Proses Produksi Larutan Viscose di PT. Indo-Bharat Rayon - Madani, Ryan; Widarman, Agung; Yudha, Haris Sandi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Products or services must be of high quality. This can make consumers satisfied and remain loyal to the goods or services produced. PT. Indo-Bharat Rayon is the first factory to produce Viscose Rayon Staple Fibers in Indonesia. However, in the process of making Viscose solution based on the results of Ball Fall value testing in March-June 2025, an Out-of-control test was found. The existence of Out-of-control test results is a strong indication of problems in quality control in the Viscose solution manufacturing process. Seeing the problems that occur, an analysis using the Statistical Process Control (SPC) method needs to be carried out. Based on the X-Chart of the Ball Fall test, the Out-of-control process occurs in data No. 1,4,7, 8,32, 72, 76,80,107,108 and No. 118. Based on the S-Chart, it occurs in data No. 4,7,32,54,80,107,108 and 118. The causes of Out-of-control in Viscose solution include: Human error, Material, Method, Machine, and Environment.